A Cloud-Connected Multi-Lead Electrocardiogram (ECG) Sensor Ring - Dong, Quan; Downen, R. Scott; Li, Baichen; Tran, Nam; Li, Zhenyu (IEEE sensors journal, 2021)
The ability to acquire multi-lead electrocardiograms (ECGs) in a timely manner is critical to patient survival and better clinical outcomes after acute cardiac events, including myocardial infarctions (MI). However, current wearable ECG devices do not provide the traditional 12-lead information needed for clinical MI diagnosis. Here, we report, to our knowledge, the first finger-ring-shaped ECG sensor that can provide asynchronously derived 12-lead ECGs by sequentially placing the ring on eight defined locations on the body. We demonstrate that the sensor performance is comparable to that of a clinical 12-lead ECG machine in a human subject study. The ring ECG sensor has an input-referred electronics noise floor of less than 10uV (peak-to-peak) with a 480X gain and a bandwidth of 0.16\sim 156 Hz. The battery lasts \sim 5 days under normal usage. The ring sensor can also wirelessly upload data to a cloud-based medical IoT informatics system via a smartphone gateway. Combined with advancements in cloud computing, telemedicine, and artificial intelligence, this on-demand IoT ECG sensor can potentially help high-risk cardiac patients reduce prehospital delays and seek timely life-saving interventions.